Esophagus cancer: a 7 - year’s Experience with 47 Cases - Schneeberger, Federico; Bergalli, Luis; Castiglioni, Juan Carlos; Torterolo, Edgardo; Rinaldi, Bruno (Cirugía del Uruguay, 1980)
Complete review of theraphy and conduct followed in the 47 cases of Esophageal Cancer treated in the Central Hospital of the Armed Forces in a 7 - year period with total follow - up. Only 7 % of ali patients survived l'onger than 3 years. The number of neoplasic recurrences ( 42,8 % ) seems to the authors to indicate that a more aggressive conduct is required, even to total extended esophagectomy.